A systematic analysis of TCA Escherichia coli mutants reveals suitable genetic backgrounds for enhanced hydrogen and ethanol production using glycerol as main carbon source. Issue 11 (14th July 2015) - Valle, Antonio; Cabrera, Gema; Muhamadali, Howbeer; Trivedi, Drupad K.; Ratray, Nicholas J. W.; Goodacre, Royston; Cantero, Domingo; Bolivar, Jorge
Abstract: Biodiesel has emerged as an environmentally friendly alternative to fossil fuels; however, the low price of glycerol feed‐stocks generated from the biodiesel industry has become a burden to this industry. A feasible alternative is the microbial biotransformation of waste glycerol to hydrogen and ethanol. Escherichia coli, a microorganism commonly used for metabolic engineering, is able to biotransform glycerol into these products. Nevertheless, the wild type strain yields can be improved by rewiring the carbon flux to the desired products by genetic engineering. Due to the importance of the central carbon metabolism in hydrogen and ethanol synthesis, E. coli single null mutant strains for enzymes of the TCA cycle and other related reactions were studied in this work. These strains were grown anaerobically in a glycerol‐based medium and the concentrations of ethanol, glycerol, succinate and hydrogen were analysed by HPLC and GC. It was found that the reductive branch is the more relevant pathway for the aim of this work, with malate playing a central role. It was also found that the putative C4‐transporter dcuD mutant improved the target product yields. These results will contribute to reveal novel metabolic engineering strategies for improving hydrogen and ethanol production by E. coli . Abstract : The low price of glycerol feed‐stocks generated from the biodiesel industry has become a burden to the industry, thus a feasible alternative is the microbial biotransformation of waste glycerol with Escherichia . In this study, E. coli single null mutant strains of the enzymes involved in tricarboxylic acid (TCA) cycle in anaerobic mode are studied. It is found that the reductive branch is susceptible for genetic modification in order to obtain higher target product yields, with malate playing a central role in anaerobic C4 metabolism. The photos used in this panel are from wikimedia Commons (photo on the left by Myrabella/Wikimedia Commons/CC‐BY‐SA‐4.0 and photo on the right by Steven Vaughn from the Agricultural Research Service, the research agency of the United States Department of Agriculture).